An overview of research on plant based natural dyes in Nepal: scope and challenges - Bhandari, Netra Lal; Pokhrel, Basant; Bhandari, Upashana; Bhattarai, Sulakshana; Devkota, Anil; Bhandari, Ganesh (Journal of Agriculture and Natural Resources, 2020)
The worldwide demand of natural dyes is of great interest due to the increased public awareness about the atmospheric and environmental pollution caused by the commercially available synthetic dyes. Nepal being wealthy in flora, would be fine research laboratory land for the plant based natural dyes. Among most of the natural dyes, plant-based dyes/pigments have wide range of applications in fabric, food, drug coloring, therapeutic values and also in solar cells in presence of different mordants. The use of mordant is inevitable during natural dyeing process in order to improve the fastness properties on fabrics, foods and drugs by forming a co-ordination complex with dye. In this article, a short overview of plant based natural dyes extraction applications and their scope and limitations will be discussed with special reference to Nepal. In the present review, the green methods of dye extraction, and dyeing technologies will be discussed, and the research fields based on natural dyes will be explored. Some of the natural dyes has also shown the antimicrobial, antioxidant, antifungal properties and hence are also discussed with biomedical applications.